Diseño de un modelo de prácticas y procedimientos de contingencias para la operación de las Centrales de Procesamiento de Fluidos (CPFs) de Campo Rubiales (2019)
The development of this Project is aimed at the implementation of a practices and procedures model of contingences for the operation of the Central Processing Facilities (CPFs) of Campo Rubiales. In the first instance, a general description of the Central Processing Facilities is done with an emphasis in the process and in the equipments used for the development of the same.